2017
DOI: 10.1111/nhs.12385
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to quality of life among older adults in Bangladesh: A cross sectional survey

Abstract: This cross-sectional design study aimed to describe quality of life and examine factors related to quality of life among older adults in Bangladesh. Convenience sampling was used to recruit 280 older adults from ten villages in two southern districts. The results demonstrate that the majority of the participants reported an overall moderate score of quality of life. Moreover, participants' sleep problems, depression, religiosity, and activities of daily living were negatively correlated with quality of life wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 25 publications
2
28
1
Order By: Relevance
“…Elders who could afford healthcare services had 4.69 times higher QOL than those who could not afford health services. A similar study conducted in Bangladesh indicated that health service affordability was found to be positively associated with the QOL of elderly people [36].…”
Section: Discussionmentioning
confidence: 88%
“…Elders who could afford healthcare services had 4.69 times higher QOL than those who could not afford health services. A similar study conducted in Bangladesh indicated that health service affordability was found to be positively associated with the QOL of elderly people [36].…”
Section: Discussionmentioning
confidence: 88%
“…Depression severity was associated with poor QOL in outpatients from Singapore [63]. Studies among the elderly from Korea and Bangladesh also reported associations between depression and lower QOL [64,65]. The only study from Nepal assessing QOL after major trauma was also among the elderly from a city area, where higher age and PTSD diagnosis were associated with poorer QOL even 1.5 years after the trauma [66].…”
Section: Discussionmentioning
confidence: 97%
“…Good social support will improve the patient's quality of life. This is because patients who have good social support can more easily convey complaints or problems so they can be resolved with a positive coping mechanism [14].…”
Section: Realtionship Between Gender and Qolmentioning
confidence: 99%